The Implementation of Bilingual Flashcards to Improve Vocabulary Mastery in Fiqh Lesson for the First Grader at SDNU Sleman Yogyakarta - Mahmud Sarifudin; Rahayu Rahayu (INOVISH JOURNAL, 2023)
This study was carried out to implement bilingual flashcards method in Fiqh learning, especially during a pandemic to the first grade students at SDNU Sleman Yogyakarta. This research method is classroom action research (CAR). The data was collected using pretest and post test which were then processed using the SPSS v.22 application. The results of these data indicate that the average change of both, before using flashcard media is 49.44 while after using flashcards media is 86.66. The increase in the average indicates a very good result. While the result of significance (tailed2) is 0.00 less than 0.05 so that it shows a significant difference between the two variables and shows a significant effect on the difference in treatment between the two variables.